The Role of Evolutionary Psychology in the Contemporary Shaping of Gender Representations - Zárate-Sánchez, Roberto (2025)
This qualitative research provides an approach, based on a critical bibliographic review, to the representations that, from some contemporary interpretations, such as those of the incels and pickup artists, Evolutionary Psychology holds. This theoretical approach considers that the human mind is composed of functional, innate, and encapsulated modules, a product of natural selection and evolution, which, according to this academic community, are the result of environmental challenges faced during the early years of the human species, particularly during the hunting-gathering period. The mind, as its founders suggest, would have a Stone Age architecture. On the other hand, from the theory of misogyny proposed by Australian philosopher Kate Manne, a series of examples are presented, especially from papers within the Evolutionary Psychology academic community, that demonstrate how representations of sexual difference can, through various interpretations, reproduce naturalized ideas about what would supposedly constitute normal psychological behavior. As concluded in the paper, these are representations that contribute to reinforcing the misogynistic structure in Manne’s sense.